Indonesia dalam Pusaran Masa Pandemi: Strategi Solidaritas Sosial berbasis Nilai Budaya Lokal - Yaspis Edgar N. Funay (Jurnal Sosiologi Agama Indonesia (JSAI), 2020)
This paper will describe and analyze the elaboration of local cultural values as a force of social solidarity in Indonesia during the current pandemic. Furthermore, the purpose of this paper will be to explore how social solidarity based on local cultural values can not only be a local resistance but can also create a space for negotiation and elaboration to find a solution in the current pandemic. Therefore, the data collection method used in the form of studying facts through literary sources will then be tested for relevance to the reality that is happening in the community. Using a cultural ethics perspective this paper will examine the extent to which values, ethics, and cultural morals can play a role in social solidarity in Indonesia. In the end, this paper will explore the elaboration of the concept of local Indonesian tradition with the policies carried out by the government as part of the concept of social solidarity and the nearest way out to maintain the survival of the Indonesian people in the midst of the current pandemic vortex.